Preliminary study on the relationship between aflatoxin-bovine serum albumin adducts in blood and aflatoxin M1 levels in milk of dairy cows - Saltzmann, J.; Xu, Y.; Gong, Y.Y.; Kersten, S.; Danicke, S.; Routledge, M.N.; Lindahl, Johanna F. (Springer, 2020)
The aflatoxin (AF) albumin adduct is often used as a biomarker for aflatoxin exposure in humans. An ELISA method previously used for aflatoxin serum albumin in human blood was used to analyse bovine serum samples (n = 22) collected from dairy cattle during an aflatoxin mitigation study in Kenya. Albumin adduct data were compared with aflatoxin M1 (AFM1) levels in corresponding milk samples from these cows. The concentration ranged from < LOD to 487.9 pg/mL for AFM1 and < LOD and 96.3 pg/mg for aflatoxin-albumin. This study indicates that aflatoxin-albumin adducts could be used as a measure of chronic aflatoxin exposure in dairy cattle.